2013
DOI: 10.2118/147306-pa
|View full text |Cite
|
Sign up to set email alerts
|

Wettability Alteration in High-Temperature and High-Salinity Carbonate Reservoirs

Abstract: DedicationTo my parents Shakuntala and Vasudev Sharma and my sister Neelam Sharma.v

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
60
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(71 citation statements)
references
References 12 publications
4
60
1
Order By: Relevance
“…Based on their polar head group, surfactants are most commonly classified in cationic (positive charge), anionic (negative charge) and nonionic (no charge). In previous studies, cationic surfactants have shown improve oil recovery by wettability alteration in oil-wet chalk rocks (Austad et al 1998;Sharma and Mohanty 2013;Zhang and Austad 2005); however, this type of surfactant requires high concentrations and is too expensive to economically be implemented on the field (Adibhatla and Mohanty 2008;Chen et al 2001). In addition, anionic and nonionic surfactants have also been studied in fracture carbonates and chalk reservoirs effectively shifting wettability and reducing IFT, improving oil imbibition (Adibhatla and Mohanty 2008;Austad et al 1998;Babadagli et al 1999;Chen et al 2001;Sharma and Mohanty 2013;Wang et al 2012;Zhang and Austad 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on their polar head group, surfactants are most commonly classified in cationic (positive charge), anionic (negative charge) and nonionic (no charge). In previous studies, cationic surfactants have shown improve oil recovery by wettability alteration in oil-wet chalk rocks (Austad et al 1998;Sharma and Mohanty 2013;Zhang and Austad 2005); however, this type of surfactant requires high concentrations and is too expensive to economically be implemented on the field (Adibhatla and Mohanty 2008;Chen et al 2001). In addition, anionic and nonionic surfactants have also been studied in fracture carbonates and chalk reservoirs effectively shifting wettability and reducing IFT, improving oil imbibition (Adibhatla and Mohanty 2008;Austad et al 1998;Babadagli et al 1999;Chen et al 2001;Sharma and Mohanty 2013;Wang et al 2012;Zhang and Austad 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Various experiments have been conducted on the study of wettability and IFT alteration using surfactants based on spontaneous and forced imbibition in carbonate and sandstone reservoirs (Adibhatla and Mohanty 2008;Austad et al 1998;Babadagli et al 1999;Chen et al 2001;Hirasaki and Zhang 2003;Sharma and Mohanty 2013;Shuler et al 2011;Wang et al 2012;Zhang and Austad 2005); however, these experiments have limited application on unconventional reservoirs due to their ultralow permeability and low porosity values. There is limited literature on the study of combined effect of wettability and the corresponding IFT alteration effect on imbibition process on core samples from unconventional plays.…”
Section: Introductionmentioning
confidence: 99%
“…Similar experimental work is not available for carbonate minerals. The carbonate rock constituent mineral, calcite, is a positively charged surface at neutral pH conditions (Somasundaran and Agar 1967;Anderson 1986). This is because of the dissolution of the surface ions from the crystal structure that leaves behind positive and negative sites that are then hydrolyzed.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the recovery by displacement tests using modified brine, with higher sulfate content but no reduction in salinity, is as high as 80% with an incremental recovery of 40% of OOIP. Contact-angle measurements were used as a screening method to narrow down the list of added surfactants that create water-wetting conditions (Sharma and Mohanty 2013). Use of added surfactants led to 70-80% recovery by imbibition, mainly attributed to wettability alteration.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have witnessed an increasing interest in surfactant mediated wettability alteration and enhanced spontaneous imbibition in oil-wet carbonates. There are a wide range of choices in the selections of surfactants: nonionic surfactants (Vijapurapu and Rao, 2004;Standnes et al, 2002;Xie et al, 2005), cationic surfactants (Austad et al, 1998;Standnes et al, 2002) and anionic surfactants (Seethepalli et al, 2004, Sharma andMohanty, 2011;Chen and Mohanty, 2013).…”
Section: Introductionmentioning
confidence: 99%